RESEARCH ON CLINICAL CHARACTERISTICS AND OUTCOMES OF TOPICAL TREATMENT WITH ZINVIO AND MEDLO IN PEDIATRIC ATOPIC DERMATITIS - Tran, Thi Minh Tam; Diep, Thang; Nguyen, Trung Kien (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Atopic dermatitis is a chronic inflammatory skin disease characterized by intense pruritus and xerosis, with a relapsing-remitting course. Although AD is most common in children, it can occur at any age. In the management of atopic dermatitis, moisturizing therapy serves as the cornerstone regardless of disease severity or stage. ZINVIO and MEDLO are moisturizers containing active ingredients such as polyhydroxy acids, dipotassium glycyrrhizinate, zinc oxide, vitamin E, sunflower seed oil, etc., which possess anti-inflammatory and antimicrobial properties, enhance the skin barrier, and help reduce the frequency of topical corticosteroid use. Objectives: 1. To describe the clinical characteristics of pediatric atopic dermatitis. 2. To evaluate the results of topical treatment with ZINVIO and MEDLO in pediatric atopic dermatitis. Materials and methods: A descriptive case series study was conducted on 74 patients under 16 years of age diagnosed with atopic dermatitis who received topical treatment with ZINVIO and MEDLO and were followed for 4 weeks. Results: The median age (interquartile range) was 6.0 years (3.9–9.3), with a female-to-male ratio of approximately 1.6/1. The median age of onset was 1 year, with 62.2% experiencing early onset before the age of 2. Pruritus was the most common symptom, observed in 100% of patients. According to the SCORAD index, moderate severity was reported in 86.5% of cases. The topical treatment outcomes using ZINVIO and MEDLO after 4 weeks showed good response in 51.4% of cases, fair in 39.2%, moderate in 5.4%, and poor in 4.1%. Erythema and pruritus were recorded as adverse effects; they were transient, occurred at a low incidence during the first week of treatment, and were not observed in the following weeks. Conclusion: Pediatric atopic dermatitis typically has an early onset before the age of 2 and is characterized by prominent pruritus, with moderate disease severity being the most common. ZINVIO and MEDLO are effective topical treatment methods that help reduce disease severity while ensuring a high level of safety.